Matrix metalloproteinases in keratinocyte carcinomas - Pilvi Riihilä; Liisa Nissinen; Veli‐Matti Kähäri (WILEY, 2022)
The incidence of cutaneous keratinocyte-derived cancers is increasing globally. Basal cell carcinoma (BCC) is the most common malignancy worldwide, and cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer. BCC can be classified into subtypes based on the histology, and these subtypes are classified further into low- and high-risk tumors. There is an increasing need to identify new therapeutic strategies for the treatment of unresectable and metastatic cSCC, and for aggressive BCC variants such as infiltrating, basosquamous or morpheaform BCCs. The most important risk factor for BCC and cSCC is solar UV radiation, which causes genetic and epigenetic alterations in keratinocytes. Similar gene mutations are noted already in sun-exposed normal skin emphasizing the role of the alterations in the tumor microenvironment in the progression of cSCC. Early events in cSCC progression are alterations in the composition of basement membrane and dermal extracellular matrix induced by influx of microbes, inflammatory cells and activated stromal fibroblasts. Activated fibroblasts promote inflammation and produce growth factors and proteolytic enzymes, including matrix metalloproteinases (MMPs). Transforming growth factor-beta produced by tumor cells and fibroblasts induces the expression of MMPs by cSCC cells and promotes their invasion. Fibroblast-derived keratinocyte growth factor suppresses the malignant phenotype of cSCC cells by inhibiting the expression of several MMPs. These findings emphasize the importance of interplay of tumor and stromal cells in the progression of cSCC and BCC and suggest tumor microenvironment as a therapeutic target in cSCC and aggressive subtypes of BCC.